Nickel black chromium coating on solar thermal collector material - Mok, Wen Shen, 1994- , author; Jamaliah Idris, supervisor 225354; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017